Durability of GFRP bars embedded in seawater sea-sand concrete: A coupling effect of prestress and immersion in seawater. (4th April 2022) - Lu, Zhongyu; Li, Shixin; Xie, Jianhe; Huang, Quanmeng; Zhang, Baifa; Huang, Peiyan; Li, Jianglin; Li, Lijuan
Highlights: The durability of GFRP bars under the combined effect of prestress and immersion in seawater was investigated. The loss of prestress applied by pre-tensioning method was monitored. The degradation mechanism was revealed from the chemical products at the interface between GFRP bar and SSC. Abstract: Using prestressed glass fibre-reinforced polymer (GFRP) bars for seawater sea-sand concrete (SSC) structures in offshore engineering is of particular interest for improving the utilisation of GFRP and natural resources. However, limited information is available on the effects of prestressing on the durability of GFRP. Therefore, the durability of SSC-coated GFRP bars was investigated under the coupling effect of prestressing and immersion in seawater at room temperature, 40 °C, and 60 °C, with prestress levels set at 20% and 40% of the ultimate tensile strength (% fu ) of GFRP. The tensile properties, interlaminar shear strength, transverse shear strength degradation after 0 d, 30 d, 60 d and 120 d, and the prestress loss of GFRP within 70 d were studied. The results showed that SSC wrapping was not conducive to the long-term performance of GFRP bars due to the alkaline environment, and the prestress further accelerated the tensile strength degradation, with the tensile strength decreasing almost to zero for the specimens (with 40% fu prestress level) immersed in seawater after 120 days at 40 °C and 60 °C. However, the interlaminar shear strength and transverse shear strength retention were 37.1% and 52.2% for 60 °C immersion under the same conditions, respectively. These findings suggest that the shear properties degenerated more slowly than the tensile properties of the prestressed GFRP bars embedded in SCC under seawater environment, which also evidences that the glass fibres were damaged more heavily than the epoxy vinyl resin under the prestressing.